2016
DOI: 10.1097/ijg.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow-up of a Novel Aqueous Humor MicroShunt

Abstract: Surgery with the InnFocus MicroShunt transscleral aqueous drainage tube with Mitomycin C achieved IOP control in the low teens in most subjects up to 3 years of follow-up with only transient adverse events occurring within the first 3 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
223
2
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(253 citation statements)
references
References 18 publications
18
223
2
10
Order By: Relevance
“…In a prospective study of 23 eyes in 14 patients with 3 years followup, Batlle et al reported a qualified success rate of 95% with a decrease in mean IOP of over 50% (23.8 mmHg to 10.7 mmHg) in addition to significant decrease in mean number of glaucoma medication [38]. The authors concluded that InnFocus MicroShunt is a safe and effective device for achieving IOP control in most subjects at 3 year follow-up.…”
Section: Subconjunctivalmentioning
confidence: 88%
“…In a prospective study of 23 eyes in 14 patients with 3 years followup, Batlle et al reported a qualified success rate of 95% with a decrease in mean IOP of over 50% (23.8 mmHg to 10.7 mmHg) in addition to significant decrease in mean number of glaucoma medication [38]. The authors concluded that InnFocus MicroShunt is a safe and effective device for achieving IOP control in most subjects at 3 year follow-up.…”
Section: Subconjunctivalmentioning
confidence: 88%
“…A study of 23 eyes with Microshunt insertion, some with and some without cataract surgery, showed that over 80% of the patients had had an IOP ≤14 mmHg at 3 years [33]. At 3 years, the number of medications had fallen from 2.6 ± 0.9 to 0.8 ± 1.2 in the eyes with Microshunt alone, and from 2.0 ± 0.9 to 0.4 ± 0.1 in the eyes that underwent a combined procedure.…”
Section: Subconjunctival Spacementioning
confidence: 99%
“…5Comparison of the pressure-lowering effect of (1) combined phacoemulsification and iStent [2], (2) combined phacoemulsification and Hydrus [16], (3) CyPass alone [25], (4) XEN 45 alone [31], and (5) InnFocus alone [33]
Fig. 6Comparison of the reduction in number of medications following (1) combined phacoemulsification and iStent [2], (2) combined phacoemulsification and Hydrus [16], (3) CyPass alone [25], (4) XEN 45 alone [31], and (5) InnFocus alone [33]
…”
Section: Subconjunctival Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Data from a 3-year long-term study showed that after the Recent Developments in Glaucoma MicroShunt procedure, mean IOP was reduced by 55% to 10.7 mmHg and more than 80% of the 22 patients had an IOP below 14 mmHg. 28 In addition, 64% of patients did not require any glaucoma medication during the third year of the study. A phase II/III study with a planned population of 857 patients is currently ongoing (NCT01881425).…”
Section: Q: What Other Emerging Technologies Have Interested You Thismentioning
confidence: 99%